Trust and privacy: How trust affects individuals' willingness to disclose personal information - Christina Heldman; Dominik Enste (Institut der deutschen Wirtschaft (IW), 2018)
Even though people regularly express concern about sharing personal information online and fear a loss of privacy, their behavior seldom matches their opinions - A phenomenon called Privacy Paradox and researched for over 20 years. Several influencing factors have been identified. A central one of these is trust, which strongly impacts the relationship between general concerns and actual behavior. This study investigates the impact of trust on the decision to disclose sensitive information online and examines the antecedents of that trust, focusing on the disposition to trust using a computerized laboratory experiment. Results indicate that dispositional trust determines the level of trust placed in the recipient of private data, especially when the person is unfamiliar with this recipient. This knowledge can be useful for business and politics in the design of marketing strategies and consumer protection policies. The study furthermore provides valuable insights on the relatedness between trust measures, which are discussed.
Keywords: C90; D91; O33; 330